TRIDHATU ALBUM: ‘DAMALUNG BLUEPRINT’ AS INSPIRATION FOR INSTALLATION ARTWORKS - Arya Aftadzila Surya (Universitas Negeri Semarang, 2025)
This study project aims to produce interactive installation artworks that represent the local wisdom values of Damalung, including spirituality, social harmony, peace, cultural preservation, and divinity. Inspired by the experimental music album Damalung Blueprint by the group Tridhatu, the works reinterpret 400 years of historical and cultural transformations in the Merbabu region. Through a creative process involving research, material experimentation, and conceptual reflection, five multisensory installations were developed. Each piece engages audiences through visual, auditory, tactile, and symbolic elements to foster reflection and dialogue. The results demonstrate that this approach effectively conveys cultural meaning while offering a profound aesthetic experience. Audience enthusiasm toward the interactivity and atmosphere of the works serves as an indicator of success. This project contributes to the discourse of contemporary art by exploring installation art rooted in local wisdom.